STUDI KEBERADAAN JENTIK NYAMUK Aedes sp. BERDASARKAN KARAKTERISTIK TEMPAT PENAMPUNGAN AIR DI KELURAHAN TUNGKAL III, KUALA TUNGKAL, JAMBI - Novrianti, Tiana; Chandra, Emilia (Ruwa Jurai: Jurnal Kesehatan Lingkungan, 2021)
Tanjung Jabung Barat is a tidal area and is one of the endemic areas for dengue fever in South Sumatra. The highest cases were in the Kuala Tungkal Health Center area, especially in Tungkal III Village. This study aimed to determine the characteristics of the container which Aedes sp. prefer as breeding places. The research was conducted using visual methods inside and outside the home and identified the characteristics of each landfill. The results showed that 54.5% (36 out of total 66 houses were inspected) and 14.9% (57 of 381 TPA inspected) found Aedes sp. Based on its characteristics, the Aedes sp. prefer to lay eggs in TPA made of plastic (16.0%), drum-type (21.3%), and without cover (18.0%). Based on water sources, larva Aedes sp. more common in landfills that collect rainwater (26.0%) and outside the house (19.1%). Limited clean water sources encourage people to use large TPAs to collect rainwater. The use of abate, periodic larva monitoring, and increasing public knowledge are actions that must be taken.Â